ANALISIS STABILITAS LERENG MENGGUNAKAN METODE BISHOP: Studi kasus: Bantaran Sungai Kali Konto Hilir, Di kabupaten Jombang - Alfatoni Alfatoni; Laily Endah Fatmawati (LPPM Universitas Bina Bangsa, 2023)
Jombang is one of the regencies in the East Java region with an area of ​​1159.50 km2. Astronomically, Jombang Regency is located between 7o20 – 7o46 south latitude and 112o03 – 112o27 east longitude. Where there is a natural river that crosses the middle which does not escape from flooding every year. One of the problems that must be addressed is the protection of the downstream Konto River bank. Prior to carrying out slope repair rehabilitation, it is necessary to have knowledge about slope stability to determine the type of soil and the form of reinforcement to be applied. For this reason, there is a need for management related to increasing the stability of river slopes. Based on sample testing in the laboratory, the most critical soil data obtained were: unit weight value ɣ (KN/m3) = 16.00 kN/m3. The internal shear angle value (Φ) = 20.00. Cohesion value (C) = 20.00. Based on the results of data processing using the Geoslope Slope/W Software with the bishop method, the FK value for dry conditions in cross sections A-A' was 1,214 and the FK value for dry conditions in cross sections B-B' was 1.9. While the FK value for the saturated cross section A-A' is 0.714 and the FK value for the saturated cross section B-B' is 0.870. Where according to Krahn, 2004 in table 2.4, the condition of the slope is safe in dry conditions and avalanches will occur when conditions are saturated. In the manual calculation of the slice method, the dry condition FK value in the cross-section A-A' is 1.6 and FK value in dry condition cross section B-B' is 1.8. This means that according to Krahn, 2004 in table 2.4 where the FK value for the overall slope is between 1.5-1.8, the slope at Kali Konto downstream is safe in dry conditions